2013
DOI: 10.1152/jn.00968.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal responses to target onset in oculomotor and somatomotor parietal circuits differ markedly in a choice task

Abstract: Kubanek J, Wang C, Snyder LH. Neuronal responses to target onset in oculomotor and somatomotor parietal circuits differ markedly in a choice task. J Neurophysiol 110: 2247-2256, 2013. First published August 21, 2013 doi:10.1152/jn.00968.2012We often look at and sometimes reach for visible targets. Looking at a target is fast and relatively easy. By comparison, reaching for an object is slower and is associated with a larger cost. We hypothesized that, as a result of these differences, abrupt visual onsets may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
6
6
0
Order By: Relevance
“…Previous studies have identified visual neurons (Andersen et al, 1985), e.g. those responding to the onset (Gottlieb et al, 1998;Kubanek et al, 2013) or offset (Ben Hamed and Duhamel, 2002) of salient or relevant targets; as well as neurons responsive to both visual target and saccadic onset (Colby et al, 1996;Gottlieb et al, 2005), with differential distribution along the dorsal-ventral extent of the macaque LIP (Chen et al, 2016). Similarly, in the marmoset PPC, we observed visual neurons responsive to fixation offset and those responsive to target onset and saccadic onset.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have identified visual neurons (Andersen et al, 1985), e.g. those responding to the onset (Gottlieb et al, 1998;Kubanek et al, 2013) or offset (Ben Hamed and Duhamel, 2002) of salient or relevant targets; as well as neurons responsive to both visual target and saccadic onset (Colby et al, 1996;Gottlieb et al, 2005), with differential distribution along the dorsal-ventral extent of the macaque LIP (Chen et al, 2016). Similarly, in the marmoset PPC, we observed visual neurons responsive to fixation offset and those responsive to target onset and saccadic onset.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have identified visual neurons (Andersen et al, 1985), e.g. those responding to the onset (Gottlieb et al, 1998;Kubanek et al, 2013) or offset (Ben Hamed and Duhamel, 2002) of salient or relevant targets; as well as neurons responsive to both visual target and saccadic onset (Colby et al, 1996;Gottlieb et al, 2005), with differential distribution along the dorsal-ventral extent of the macaque LIP (Chen et al, 2016). Similarly, in the marmoset PPC, we observed visual neurons responsive to fixation offset and those responsive to target onset and saccadic onset.…”
Section: Discussionsupporting
confidence: 72%
“…The activity can be thought of as representing priority (Bisley and Goldberg 2010), salience (Gottlieb 2007), or a form of value (Kubanek and Snyder 2015;Louie et al 2011;Louie and Glimcher 2010;Sugrue et al 2004), but in all cases it is used to decide where to place covert (Bisley and Goldberg 2003; Herrington and Assad 2010) and overt (Ipata et al 2006;Kubanek et al 2013;Mazzoni et al 1996) attention. We do not wish to use the present data to reopen the debate and claim that LIP activity represents motor planning and not attention; instead we suggest that the guidance of visuospatial attention is part of the process of deciding where to look.…”
Section: Discussionmentioning
confidence: 99%